Extinção e prorrogação dos contratos de concessão de serviços públicos - Losinskas, Paulo Victor Barchi (2016)
This thesis has as an object the study and deepening of the entire legal framework regarding the extinction of public service concession contracts and, also, the possibility of prorogation of these agreements. The goal is to identify the forms of termination, the mechanisms established by law to do so, as well as the consequences that present themselves right after the extinction of the contract. It also intends to present and organize all the possibilities that are available to the Public Administration at the conclusion of a concession pact, in order to maintain the provision of an adequate public service, as defined by constitutional force. Therefore, first it s necessary to verify all the details of the concession contract, defining its purpose and its fundamental clauses, without which it s inconceivable to have complete comprehension of the subject. Afterwards, aware of the contractual assumptions, it s feasible to discriminate the ways that the contract can be extinct and its causes, with the respective reflection in the rights of the service provider, as well as the granting authority. Finally, knowing the forms of contract termination, it´s mandatory to analyze how the provision of public services might continue; from the possibility of extending the same contract already in place, to the transfer of this obligation to agencies or government entities or, even, the event of a new process of selection of a concessionaire, through bidding, which is the instrument able to provide the specific choice of best proposal and best bidder.